2015
DOI: 10.1111/tid.12410
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus bacteremia in a kidney transplant recipient

Abstract: Lactobacillus rhamnosus is a rare clinical pathogen. A case of bacteremia caused by L. rhamnosus in a kidney transplant recipient is described. Once considered only as a contaminant or a low-virulence organism, L. rhamnosus might be an opportunistic pathogen in immunocompromised patients. To our knowledge, this is the first report of primary bloodstream infection caused by L. rhamnosus in a kidney transplant recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Cases have been reported in transplant recipients and in patients with acute leukemia, uncontrolled diabetes mellitus, and chronic renal failure. 2 , 3 Other predisposing events and behaviors linked with Lactobacillus bacteremia include prolonged use of broad-spectrum antibiotics, dental manipulations and poor dental hygiene, as well as intravenous drug abuse. Use of probiotics has been reported as a potential source of Lactobacillus bacteremia in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been reported in transplant recipients and in patients with acute leukemia, uncontrolled diabetes mellitus, and chronic renal failure. 2 , 3 Other predisposing events and behaviors linked with Lactobacillus bacteremia include prolonged use of broad-spectrum antibiotics, dental manipulations and poor dental hygiene, as well as intravenous drug abuse. Use of probiotics has been reported as a potential source of Lactobacillus bacteremia in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only two more case reports in the literature reporting primary bloodstream infection caused by Lactobacilli spp. in a kidney transplant recipient [12,13]. Vanichanan et al reported a 60-yearold renal transplant recipient who developed an intra-abdominal abscess which grew a carbapenem-resistant Lactobacillus casei (L. casei), with an uneventful follow-up course for four years.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a concern of the probiotic bacteria or fungus used in food production to translocate and cause systemic infections in immunocompromised transplant recipients. Available literature is limited to case reports or case series and use in circumstances where there may be an opportunity for translocation such as mucosal interruption or altered gastrointestinal blood supply during periods of hemodynamic instability 49‐51 . Most of the published literature demonstrates an association between exposure and this risk; however, there is potential for gene exchange and promotion of antibiotic resistance with use 51 .…”
Section: Over‐the‐counter Medicationsmentioning
confidence: 99%